PSYCHOLOGY OF NORTH SUMATRA PENCAK SILAT PELATDA ATHLETES TOWARDS PON XXI - Keliat, Pedomanta (Indonesia Sport Journal, 2023)
In facing this big event which is held every 4 years, the National Sports Week is a place to "show off" for sports people in Indonesia. There are many things that need to be prepared, starting from the venue, competition equipment, supporting infrastructure to the community's readiness to welcome this "Party". Several factors influence athletes to be able to achieve achievements in a sporting event, including physical readiness, intensive training, strategic maturity and mental health to compete. Not infrequently mentality is a determining factor in competition. Long training and physical abilities as well as good strategies will be destroyed in the competition arena if the athlete's own mental state is not developed. Athletes' mental health will become increasingly disturbed as the match gets closer. A good coach certainly prepares and pays attention to his team's children from all aspects.In an effort to provide mental development for athletes, this research tries to identify facts in the field. This research data will be taken factually from individual athletes using a personal approach and also questionnaires as data support. The results of the research will show how each athlete's mental health is before competing, so that coaches can take steps to encourage, motivate and indoctrinate athletes who have mental disorders. Anxiety, fear, decreased concentration, lack of self-confidence, lack of enthusiasm, lost aggressiveness, and even intelligence in competition are mental factors that influence performance in the arena. If these factors can be minimized as early as possible, then 75% of athletes' wins are in sight. A healthy mentality when competing will greatly influence your performance. No matter how strong the opponent is, it will be very easy to beat if the athlete has a good mentality.The aim of this research is to provide accurate information regarding the mental state of North Sumatra Pencak Silat Pelatda athletes in 2023 in preparation for the XXI PON competition.